Development of a user-based usability evaluation tool for mobile health (mHealth) systems - Portus, Alyssa Jean
The Philippine government aims to promote the development of local non-invasive medical devices in the country. Part of the medical device development is the usability evaluation of such devices to ensure effectiveness, efficiency, and safety of use. Due to the limited number of usability experts in the country, this study aims to develop a formative usability evaluation tool that can be administered by non-usability experts (e.g. medical device developers) to identify problematic areas on the interface of an mHealth system being developed. This research proposed a user-based evaluation tool, in the form of a standardized usability questionnaire. The proposed questionnaire was used by 36 potential users to evaluate an mHealth system that provides medical assistance to patients with cardiovascular diseases. The same system was also evaluated by four usability experts using a traditional usability methodology - heuristic evaluation. The results show that the users, through the use of proposed tool, were able to determine 88.23% of the problem areas detected by experts, with all of the high priority problem areas detected. The tool was able to uncover significantly more low priority problem areas, as expected from user-based evaluations. Overall, the proposed tool can be used by medical device developers to determine high priority and low priority usability problem areas in a mobile health system.